TECHNOLOGY-BASED MEDIA USED IN TEACHING LISTENING SKILLS - Maulina, Maulina; Ignacio, Jerico Feliciano; Bersabe, Lejhana Andrea C.; Serrano, Apple Jane Dj.; Carpio, Naicellyn G.; Santos, Erica G. Dellos (Universitas Muhammadiyah Makassar, 2022)
This paper shows the effectiveness of technology-based media designed for listening skills. The effectiveness of different technology-based media is gaining importance to students and teachers. They are the main subjects in this paper because the problem that arises at school where learning English as their second language addresses the decreased potential for the succession of learning. This study mentioned the difficulties in English as they struggle to reach success learning even there are other materials to use, like media belonging to not technology-based. That is why technology-based media was introduced to students and teachers. The researchers on different studies have taken by the chosen media recognized the ability to listen for the learning of students and the teaching of teachers in their language learning. Listening could increase the potential of learning English by hearing it through devices played by technology. The paper highlights five media for listening skills that are operating through technology. They involve mobile-based media, multimedia technology, radio news, podcast application, and mobile-based audiobooks. All of them result in the practical listening skills of teachers and primarily to students.